SUPPLEMENTARY OF COCONUT PUPL EXTRACT TO FEED TO INCREASE GROWTH OF SALINE TILAPIA - Adni Oktaviana; Aldi Huda Verdian; Rahmadi Aziz (JURNAL PERIKANAN TROPIS, 2022)
Various problems are found in aquaculture activities while decreasing production due to fish disease attacks and slow growth. Various alternatives can be applied by cultivators, one of which is the use of prebiotics. Coconut pulp contains galactomannan which serves as prebiotic and belongs to agricultural waste usually used as animal feed. This study aimed to determine the level of growth and survival rate of saline tilapia (O. Niloticus) after given coconut pulp extract. A completely randomized design (CRD) was emplyed. This study consisted of three treatments with three replications. Treatment A (maintenance of saline tilapia without adding coconut pulp extract), Treatment B (rearing saline tilapia with the addition of 1% / kg of feed with coconut pulp extract), and Treatment C (rearing saline tilapia with the addition of 2% / kg of feed with coconut pulp extract). The parameters observed were growth, survival and water quality. The results of growth and survival parameters on this study were not significantly different among each treatment. Daily growth rate (DGR) was obtained in treatment C, namely LPH 1.28%. The highest survival rate was obtained in treatment B, namely 80%.Keywords: nile tilapia, coconut pulp ekstract, galactomannan